The readiness of e-Filing implementation among UiTM Shah Alam's staff / Afnil Syahriwan Ahmad Meri - Ahmad Meri, Afnil Syahriwan (2006)
This study was done to ascertain the readiness of E-Filing implementation among UiTM Shah Alam's staff concerning with the awareness, internet usage, knowledge of ICT. The major purpose of this study is to identify the readiness of staff in using this system and to define factors that encourage them to use this system. A survey was done to fulfill the objective of this study. 150 respondents were selected for the survey; consist of both academic and non-academic staff in UiTM Shah Alam A set of questionnaire was designed as the instrument for this study. The findings of the study support the notion that UiTM Shah Alam's staff is ready to apply the E-Filing system in the form of their awareness, internet usage and ICT knowledge.